Identification and Biotechnical Potential of a Gcn5-Related N-Acetyltransferase Gene in Enhancing Microalgal Biomass and Starch Production - Li, Zhongze; Cao, Li; Zhao, Liang; Yu, Lihua; Chen, Yi; Yoon, Kang-sup; Hu, Qiang; Han, Danxiang (Frontiers in Plant Science, 2020)
Microalgae are promising feedstocks for starch production, which are precursors for bioenergy and chemicals manufacturing. Though starch biosynthesis has been intensively studied in the green alga Chlamydomonas reinhardtii, regulatory mechanisms governing starch metabolism in this model species have remained largely unknown to date. We proposed that microalgal cells can regulate triacylglycerol (TAG) biosynthesis through triggering starch biosynthesis. In accordance with the hypothesis, it was observed in this study that overexpression of the plastidial lysophosphatidic acid acyltransferase gene (i.e. LPAAT1) in C. reinhardtii significantly enhanced TAG biosynthesis under nitrogen (N)-replete conditions, whereas the starch biosynthesis was enhanced in turn under N depletion. By the exploitation of transcriptomics analysis, a putative regulatory gene coding Gcn5-related N-acetyltransferase (GNAT19) was identified, which was up-regulated by 11~12 times in the CrLPAAT1 OE lines. Overexpression of the cloned full-length CrGNAT19 cDNA led to significant increase in the starch content of C. reinhardtii cells grown under both N-replete and N-depleted conditions, which was up to 4 times and 26.7% higher than that of the empty vector control, respectively. Moreover, the biomass yield of the CrGNAT19 OE lines reached 1.5 g L-1 after 2 days under N-depleted conditions, 72% higher than that of the EV control (0.87 g L-1). Overall, the yield of starch increased by 118.5% in CrGNAT19 OE lines compared to that of the control. This study revealed the great biotechnical potentials of an unprecedented GNAT19 gene in enhancing microalgal starch and biomass production.